PERBERDAYAAN KEPALA ADAT DALAM PENYELESAIAN SENGKETA TANAH KAMPUNG DOYO BARU DISTRIK WAIBU KABUPATEN JAYAPURA - Herniati , Herniati; Hartini , Sri Iin; Reliubun, Idris Firmansyah; Ingsaputro, Muhammad Hafiz (JURNAL PENGABDIAN PAPUA, 2023)
Legal counseling was carried out by the Extension Team from Doctor Husni Ingratubun University, with the title "Empowerment of Traditional Heads in Resolving Land Disputes in Doyo Baru Village, Waibu District, Jayapura Regency, the purpose of the activity is to provide understanding to the community that disputes that occur in the community, including land settlements, can be resolved through non-litigation channels by empowering the role of ondoapi/customary heads. This community service activity was carried out on Monday, August 7 2023 in the Hall of the Head Office of Doyo Baru Village, Maibu District, Jayapura Regency. The method of implementing this service is carried out by way of lectures, discussions, question and answer and ends with consultation and assistance to the community who require a more in-depth explanation from the resource person. The result of this activity was an excellent increase in the understanding of the participants, which was evident from the results of the question and answer discussion between the participants and the resource person. Keywords: Dispute; Land; Non-litigation